PELAKSANAAN SISTEM PEMERINTAHAN DESA BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2004 DIDESA KALICINTA KECAMATAN KOTABUMI KABUPATEN LAMPUNG UTARA - Sari, Erna; Neta, Yulia (FIAT JUSTISIA)
Village Administration System implementation as stipulated in the Act Law Number 32 Year 2004 on Regional Government to give freedom to the village to have a genuine authority in managing the household itself. The village also has a delegated power as deconcentration of the government on it. As the embodiment of democracy, the rule penyelenggarakan village consultative body established villages or other designations in accordance with the culture that flourished in their local village, which serves as the regulatory agencies in the governance of the village.Â Keywords: Village, Village Governance System Implementation